PENGARUH AKTIVA PAJAK TANGGUHAN DAN BEBAN PAJAK TANGGUHAN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2019 – 2021 - Tabita Theresia Panjaitan; Remista Simbolon (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2022)
The study was conducted to provide an empirical explanation the impact of deferred tax assets and deferred tax expenses on tax avoidance in various industrial sector companies that listed on Indonesia Stock Exchange in 2019 -2021. The total of population were 33 companies and the sample that fit to the criteria were 24 companies. Because the research period is three years, so the total samples is 72 data. The data has been collected and then processes using SPSS 25 with descriptive statistical data analysis,classical assumption test, and hypothesis test. The results of this study state that partially deferred tax assets have no significant influence on tax avoidance, and deferred tax expenses also has no significant influence on tax avoidance. Simultaneously deferred tax assets and deferred tax expenses does not have any influence on tax avoidance. Keywords: Tax Avoidance, Deferred Tax Assets, Deferred Tax Expenses.